Malang City Polytechnic Web Based Student Attendance Information System Telecommunications Engineering Study Program Using Fingerprint - Selvia Junika (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2019)
This research is design of an Attendance Information System titled “Malang City Polytechnic Web Based Student Attendance Information System Telecommunications Engineering Study Program Using Fingerprint”. Students of Malang City Polytechnic are still using a manual attendance system. The attendance system that is still manual has many disadvantages such as data processing, report making and also difficult to monitor student attendance. Therefore, the existence of this system makes it easy to find out student attendance on that day, because it is timely or real time. This system also makes it easy to make monthly reports about student attendance and delay. The design of this system uses PHP Web and MySQL Database connection. The results of this system can create and display monthly reports that have been processed and can monitor student attendance every day.